RANCANG BANGUN POMPA HIDRAM UNTUK MASYARAKAT PEDESAAN - Herlambang, Arie; Wahjono, Heru Dwi (Jurnal Air Indonesia, 2006)
Environmental contamination and global climate change cause degradation of fresh water in the whole world. Increasing of oil price also insist the water treatment operational cost rise, especially for pumping and water lifting from the low land areas to up land. One of alternatif solution to reduce operational cost is using Hydraulic ram pumps (hydram pump). Hydram pump are water-lifting devices that are powered by filling water. Such pumps work by using the energy of water falling a small height to lift a small part of that amount of water to a much greater height. In this way, water from a spring or stream in a valley can be pumped to a village or irrigation scheme on the hillside. The main and unique advantage of hydram pumps is that with a continuous flow of water, a hydram pump operates automatically and continuously with no other external energy source - be it electricity or hydrocarbon fuel. It uses a renewable energy source (stream of water) mid hence ensures low running cost. Minimum up lifting vertical power of pump is twice than vertical distance of water down and maximum up lifting vertical power is twenty times than vertical distance of water down. If there are air captured in distribution pipe, it will need release valve. In this paper, different aspect of designing a hydraulic-rain pump system is discussed. Application and limitation of hydram pump is presented. It imparts absolutely no harm to the environment Hydraulic ram pumps are simple, reliable and require minimal maintenance. All these advantages make hydram pumps suitable to rural community water supply and mud backyard irrigation in developing countries. Kata Kunci : Air bersih pedesaan, pompa hidram, pengelolaan air bersih.